2011
DOI: 10.1007/s11103-011-9730-z
|View full text |Cite
|
Sign up to set email alerts
|

OsBC1L4 encodes a COBRA-like protein that affects cellulose synthesis in rice

Abstract: Plant morphogenesis is highly dependent on the regulation of cell division and expansion. The organization of the cellulose microfibrils in the cell wall is a key determinant of cell expansion. Previously, a dwarf mutant with fewer tillers, Osbc1l4 (Oryza sativa brittle culm 1 like 4), was identified by screening a rice T-DNA insertion mutant library. It is reported here that OsBC1L4 encodes a COBRA-like protein that exhibits typical structural features of a glycosylphosphatidylinositol-anchor protein. The T-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 66 publications
4
52
0
Order By: Relevance
“…5). It has been shown that the reduction of cellulose in the cobra mutant is accompanied by overproduction of starch, preventing osmotic stress by the excess of glucose that cannot be incorporated into the cell wall (36). Analysis of galacturonic acid (GalA) levels revealed a significant increase in the cobra mutant (Fig.…”
Section: Volume 289 • Number 50 • December 12 2014mentioning
confidence: 97%
“…5). It has been shown that the reduction of cellulose in the cobra mutant is accompanied by overproduction of starch, preventing osmotic stress by the excess of glucose that cannot be incorporated into the cell wall (36). Analysis of galacturonic acid (GalA) levels revealed a significant increase in the cobra mutant (Fig.…”
Section: Volume 289 • Number 50 • December 12 2014mentioning
confidence: 97%
“…In other developmental contexts, COBL gene products have been shown to affect crystalline cellulose deposition (Schindelman et al, 2001;Li et al, 2003;Dai et al, 2011). Schindelman and colleagues elegantly employed polarized light microscopy to demonstrate a substantial reduction in crystalline cellulose deposition at the elongation zone of cob-1 mutant roots under restrictive conditions, a phenotype associated with the perturbation in anisotropic cell expansion (Schindelman et al, 2001;Roudier et al, 2005).…”
Section: Cobl2 Is Required For Crystalline Cellulose Deposition Intomentioning
confidence: 99%
“…Mutations in cobra (cob) result in reduced levels of crystalline cellulose and disorganized deposition of cellulose microfibrils at the root elongation zone, leading to short and swollen roots (Benfey et al, 1993;Hauser et al, 1995;Schindelman et al, 2001;Roudier et al, 2005;Sorek et al, 2014). Other characterized COBL family members have been assigned similar functions in other contexts: COBL9, in root hair elongation (Parker et al, 2000;Ringli et al, 2005;Jones et al, 2006), COBL10 and 11 in pollen tube elongation through the transmitting tract , and COBL4, initially identified through its coexpression with CESA4, CESA7 and CESA8 (as well as its orthologs from rice and maize) in secondary cell wall deposition in xylem cells (Li et al, 2003;Brown et al, 2005;Persson et al, 2005;Ching et al, 2006;Sato et al, 2010b;Dai et al, 2011;Liu et al, 2013). Of the twelve COBL family members, seven remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Transcript levels were normalized with the ACTIN transcription and relative expression levels were compared with that in Nip (set as 1), respectively. Mean values were calculated from three independent experiments and error bars indicate SD. of COBRA in rice, regulates the synthesis of secondary cell wall and affects the mechanical strength of rice plants (Li et al, 2003;Dai et al, 2011). However, SRL1 belongs to none of these groups and does not contain any conserved domain.…”
Section: Srl1 Is a Putative Gapmentioning
confidence: 99%